Efektivitas Bimbingan Pribadi-Sosial Untuk Mengembangkan Kompetensi Intrapersonal Peserta Didik (Jurnal Bimbingan dan Konseling Islam, 2015)
This purpose of this research was to produce effective social-personal guidance and developing intrapersonal competence of learners. This method that has been used quasi-experimental methods with nonequivalent control group design using purposive sampling technique. The instrument used in this research is questionnaire intrapersonal competence. The participants of this research were 70 students class X SMKN 1 Purwakarta academic year 2014/2015, amounting 70 for experiment class and 35 for control classes. Data were analyzed using t test. The results showed that the personal social guidance of the development of student’s ability in intrapersonal competencies students class X SMKN 1 Purwakarta academic year 2014/2015. The result of the study recommended to the school management, counseling teachers and for the next research.